2011
DOI: 10.1016/j.ast.2010.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive backstepping control for optimal descent with embedded autonomy

Abstract: This version is available at https://strathprints.strath.ac.uk/28957/ Strathprints is designed to allow users to access the research output of the University of Strathclyde. Unless otherwise explicitly stated on the manuscript, Copyright © and Moral Rights for the papers on this site are retained by the individual authors and/or other copyright owners. Please check the manuscript for details of any other licences that may have been applied. You may not engage in further distribution of the material for any pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Therefore, e i1 → 0 and e i2 = z i2 − k 1 e i1 − r i → 0 as t → ∞. Remark 1: Compared with the results in [19], [20], our results do not need the assumption that no input saturation occur after finite time. Moreover the asymptotic stability is achieved under the proposed controllers instead of uniform ultimate bounded stability.…”
Section: A Backstepping Control Designmentioning
confidence: 57%
See 3 more Smart Citations
“…Therefore, e i1 → 0 and e i2 = z i2 − k 1 e i1 − r i → 0 as t → ∞. Remark 1: Compared with the results in [19], [20], our results do not need the assumption that no input saturation occur after finite time. Moreover the asymptotic stability is achieved under the proposed controllers instead of uniform ultimate bounded stability.…”
Section: A Backstepping Control Designmentioning
confidence: 57%
“…By incorporating the command filter and adaptive control technique, Farrel et al [17] and Sonneveldt et al [18] solve the input saturation problem in aircraft adaptive flight control design. In [19], Li et al propose an adaptive backstepping control algorithm for optimal descent tracking. Recently, Zheng et al present the robust adaptive backstepping control schemes for autonomous attitude cooperative control to overcome the input constraint, model uncertainties, and external disturbances in [20].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The DOB that serves as a compensator is incorporated with backstepping technique. In Li, Jing, Macdonald, and Mcinnes (2011), an adaptive backstepping control law was proposed to track the optimal descent orbit and attitude trajectories. It is shown that this control law is robust against the input saturation and unknown bounded disturbance.…”
Section: Introductionmentioning
confidence: 99%